Supplemental Material: Thermotectonic events recorded by U-Pb geochronology and Zr-in-rutile thermometry of Ti oxides in basement rocks along the P2 fault, eastern Athabasca Basin, Saskatchewan, Canada - Erin Adlakha (10777711); Keiko Hattori (10777717) (2021)
Appendix figures and tables; U-Pb data set for rutile and anatase from the P2 fault.